MAPPAKALEBBI’ BALI BOLA PADA MASYARAKAT BUGIS BONE SUATU KAJIAN LIVING HADIS - Muhammad Asriady (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2016)
The underlying question in this research is how Mappakalebbi' Bali Bola at the Bugis Bone observed on Living-Hadis. The spirit born from a variety of community Bugis Bone lifes which assessed in line with the traditions of the Prophet. Practice is in line with the traditions of the Prophet that mappakalebbi' bali bola. The method used is multidisciplinary approach then in the implementation of these studied used the method Living Hadis. This study aims to assess the Bugis culture of Bone mappakalebbi' especially those in mappakalebbi' bali bola (neighbor glorify). And assesses the quality of Prophetic traditions and integrate them. In addition, this study also seeks hoped can be new spirit to implement religious values in the cultural practice of Bugis Bone. Collaboration Bugis tradition and  the culture will make people more nuanced religious awareness but cannot be separated from its essence as an always adherent with culture of the Bugis community Bone practice mappakalebbi’ values and became obedient as religious actors. If the Bugis Bone practicing Islamic values in the local culture, then the public will be more civilized, ethical and noble